2002
DOI: 10.1046/j.1528-1157.2002.15001.x
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Negative Myoclonus in a Newborn with Hemimegalencephaly

Abstract: Summary: Purpose:We report the case of a male newborn with Ohtahara syndrome and right hemimegalencephaly who presented epileptic negative myoclonus in the first days of life.Methods: Prolonged polygraphic studies were performed, as well as MRI and a full clinical examination.Results: EEG showed a constant and nonreactive pattern of burst suppression. There were several kinds of electro-clinical seizures (generalized myoclonia, short atonias, typical spasm and tonic spasms) at the beginning of the EEG's burst.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…ENM is a rare epileptic condition whose exact physiopathology remains unresolved. It has been associated with very diverse clinical situations, such as ABPE, cortical malformations, antiepileptic drug tapering, or more recently hemimegalencephaly 2,3,[5][6][7] . The intensity of the clinical manifestations may be markedly variable, and it may oscillate from slight focal atonia to severe gait disturbances originating pseudoataxia 8 .…”
Section: Discussionmentioning
confidence: 99%
“…ENM is a rare epileptic condition whose exact physiopathology remains unresolved. It has been associated with very diverse clinical situations, such as ABPE, cortical malformations, antiepileptic drug tapering, or more recently hemimegalencephaly 2,3,[5][6][7] . The intensity of the clinical manifestations may be markedly variable, and it may oscillate from slight focal atonia to severe gait disturbances originating pseudoataxia 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The association of infantile spasms, myoclonias, and partial epilepsy in newborn infants is generally observed in cases with extensive migration disorders diagnosed as Ohtahara syndrome. Guzzeta et al 30 reported the case of a male newborn with Ohtahara syndrome and right hemimegalencephaly who presented epileptic negative myoclonus on the 1st day of life. Dietrich et al 29 described three children with hemimegalencephaly among eight patients with early-infantile epileptic encephalopathy with suppression bursts.…”
Section: Casementioning
confidence: 99%
“…They may be of partial onset, infantile spasms, epilepsia partialis continua or drop attacks (7,11) . Non-convulsive status epilepticus and atypical seizure types are related in the literature and some authors had reported epileptic negative myoclonus (18,19) .…”
Section: Introductionmentioning
confidence: 99%